2010
DOI: 10.1001/archpediatrics.2010.144
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious Fatigue in Adolescents and Physical Activity

Abstract: To compare adolescents who do and do not recover from acute infectious mononucleosis in terms of fatigue severity and activity levels before, during, and in the 2 years following infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Indeed, the only differences seen were at the 6month and 12-month time points, at which adolescents with CFS napped more during the day [75]. Indeed, the only differences seen were at the 6month and 12-month time points, at which adolescents with CFS napped more during the day [75].…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, the only differences seen were at the 6month and 12-month time points, at which adolescents with CFS napped more during the day [75]. Indeed, the only differences seen were at the 6month and 12-month time points, at which adolescents with CFS napped more during the day [75].…”
Section: Resultsmentioning
confidence: 91%
“…We found no unique mechanism(s) to explain the similarly reduced peakV O 2 in adolescents with chronic fatigue or chronic pain other than deconditioning, though we cannot exclude cortical/volitional influences perhaps prompted by altered perceptual responses to vigorous activity. matched controls (28); whereas another found that days spent in bed since the onset of infectious mononucleosis was a predictor of subsequent chronic fatigue (29). Similarly, there is overlap in clinical presentation of patients with chronic fatigue and chronic pain, fibromyalgia being the entity most studied (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…One prospective case-control study found significantly greater amounts of time spent sleeping in young people with CFS compared to matched (age and Tanner stage) non fatigued controls after Epstein Barr Virus (Katz et al, 2009;Huang et al, 2010). When maintaining similar levels of exercise as the mononucleosis-recovered controls (6 months after diagnosis), young people with CFS reported significantly higher levels of fatigue and spent significantly more time sleeping during the day 6 and 12 months following infection.…”
Section: Sleepmentioning
confidence: 99%